Analisis Absensi Online Berbasis WEB Pada Pegawai Balai DIKLAT Medan - Khairunnisa; Al Afkari Siahaan, Ahmad Taufik; Maimuna Harahap; Habbani Nasution , Yazid Hulaini (IAI Nasional Laa Roiba Bogor, 2024)
Absenteeism has a significant impact on work productivity in achieving organizational goals, especially in government organizations that provide services to the community. The aim of creating this WEB-based online attendance is to make it easier for employees to fill in attendance and increase their disciplinary attitude and make the attendance results obtained more detailed and orderly. Since the waterfall technique is a structured and methodical approach to developing information systems, each step must be completed in the correct order. The methodology is based on the five processes of the waterfall method: analysis, design, testing, implementation, and evaluation. Increasing the precision and effectiveness of attendance monitoring is one advantage of implementing the Waterfall approach when creating a web-based employee attendance information system. Having a web-based attendance information system can help employees take attendance effectively and improve the previous attendance system.